1985
DOI: 10.3109/10826088509044939
|View full text |Cite
|
Sign up to set email alerts
|

Medically Induced Drug Addiction

Abstract: Iatrogenic, or medically induced, drug addiction is a problem affecting both patients and physicians. We describe the function of a new center devoted solely to managing iatrogenic addiction. The center accepts patients on physician referral only. The addiction usually arises as a complication of a medical disorder that is accompanied by pain and requires comprehensive and multidisciplinary evaluation and treatment. Detoxification from the offending medication, provision of chronic analgesia, and maintenance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The influence of opioid on escalation of adverse gastrointestinal symptoms has been recently reported. 5 Mercadante et al presented a prospective multicenter study, in which 22 patients who underwent NCPB were followed until death. NCPB was effective in reducing opioid consumption and gastrointestinal adverse effects for at least 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of opioid on escalation of adverse gastrointestinal symptoms has been recently reported. 5 Mercadante et al presented a prospective multicenter study, in which 22 patients who underwent NCPB were followed until death. NCPB was effective in reducing opioid consumption and gastrointestinal adverse effects for at least 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although this approach should be applied in every case when no alternative is available, it should be mentioned that opiates present significant number of physical and psychological complications, including drowsiness, constipation, vomiting, deteriorated communication with family and depression. 4,5 In rare cases of longer survival, iatrogenic addiction can be observed, adding to the cachectic picture of the disease. 5 Thus, more invasive methods of pain control need to be considered in IPC patients, including neurolytic coeliac plexus block (NCPL) and videothoracoscopic splanchnicectomy (VSPL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exemplar study reported that patients fell into three groups of pain types and locations (back pain, head pain and other) and a mean chronicity of pain of 8.6 years (SD 7.8) [ 92 ]. While most studies examined patients who had persistent pain despite continuous opioid use, some [ 47 , 52 , 56 , 57 , 69 , 73 , 76 , 93 , 103 , 112 ] attempted to examine specifically patients who had evidence of opioid use disorder in the context of chronic pain. Other terms used in the studies included opioid dependence, drug dependence/addiction, and narcotic addiction, but for the purposes of this paper we grouped these under opioid use disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Also, iatrogenic addiction can be observed in patients with longer survival. 2,17 This study addresses an important issue about the best time to perform neurolytic plexus block to achieve effective control of abdominal or pelvic cancer pain. The authors postulated that sympathectomy before the Fig.…”
Section: Discussionmentioning
confidence: 99%